Optimization of an Intermittent Finger Endurance Test for Climbers Regarding Gender and Deviation in Force and Pulling Time - Augste, Claudia; Winkler, Marvin; Künzell, Stefan (Frontiers in Sports and Active Living, 2022)
Performance diagnostics of finger strength is very relevant in climbing. The aim of our study was to find modalities for an intermittent finger flexor muscle endurance test that optimize the correlation of test performance with lead climbing performance. 27 female and 25 male climbers pulled with 60% MVC and a work-to-rest ratio of 7:2 s on a fingerboard until fatigue. The highest correlations, R = .429, were found for women when 9% deviation in the required force and 1 second deviation in the required pulling time was tolerated. For men, the optimum was reached with the same time deviation and a force deviation of 6%, R = .691. Together with maximum finger strength the repetitions explained 31.5% of the variance of climbing ability in women and 46.3% in men. Consequences from our results are to tolerate at least 7% force deviation for women and 5% for men and to terminate the finger endurance test quickly after the force falls below the threshold.